Effect of pasta consumption obtained by an old Italian durum wheat variety on cardiovascular parameters: an intervention study - Ghiselli, Lisetta; Sofi, Francesco; Whittaker, Anne; Gori, Anna Maria; Casini, Alessandro; Abbate, Rosanna; Gensini, Gian Franco; Dinelli, Giovanni; Marotti, Ilaria; Benedettelli, Stefano (Progress in Nutrition, 2014)
Aim this study was to evaluate the influence of short-term dietary intake of pasta obtained by an old Italian durum wheat variety on parameters related to the atherosclerotic process.  Twenty subjects were followed for 10 weeks a diet containing 70 g/die of test pasta (Test period) and for the same period a control pasta (Placebo period). The test period determined a significant improvement of total cholesterol (-10.3%; p=0.04), whereas no significant changes during the placebo period have been observed. With regard to haemorheological parameters, the test period significantly ameliorated whole blood viscosity at high shear rate (pre: 4.5 vs. post: 4.3 mPA*s; p=0.04) as well as erythrocytes’ deformability (pre: 9.8 vs. post: 10.3; p=0.03). In conclusions, dietary intake of pasta obtained by an old variety of wheat seems to impose favourable biochemical changes, with regard to lower circulating levels of markers of atherosclerosis, such as lipid parameters, and haemorheological variables.